Domestic Violence: Parent’s Perception about Child Abuse - Sari, Wilujeng Fitriana; Handayani, Sri Sularti Dewanti (Universitas Negeri Semarang, 2016)
The number of child abuse cases in Indonesia is increasing every year. The perpetrators of child abuse are mostly the parents. It is important to understand various types of domestic violence because home is children’s first environment where they learn many things. Besides that, home is a safe place for children, with parents as the main actor who guards them. The limited facility that can be used as information source of what should be done by parents in parenting and educating children is alarming. Therefore, research to identify and to analyse parents’ understanding about domestic violence is needed. This research was conducted using descriptive qualitative method in which researchers analyse further about parents’ perception about child abuse. The result from 3 participants of this research is that child abuse still exists and is done intentionally by parents with different educational and economic background.